From theory to practice: a photographic inventory of museum collections to optimize collection management - Merckx, Jonas; Van Roie, Martijn; Gómez-Zurita, Jesús; Dekoninck, Wouter (Biodiversity Informatics, 2018)
The digitization of museum specimens is a key priority in the Digital Era. Digital databases help to avoid unnecessary manipulation hazards to delicate collections, increase their accessibility to third party researchers, and contribute to the ongoing documentation of global biodiversity. Time, workforce and the need of specialized infrastructures limit the processing of the vast number of specimens in natural history collections. Cheaper, easy-to-use methods and volunteer programs are developing quickly to help bridge the gap. We present the results of combining citizen science for the digitization of an entomological collection in conjunction with the cooperation of a taxonomic expert for the remote identification of samples. In addition, we provide an assessment of the avoided monetary costs and the time needed for each step of the process. A photographic inventory of specimens belonging to the leaf beetle genus Calligrapha was compiled by volunteers using a low-cost compact camera and the species were identified using these images. Using digital photographs allowed for a rapid screening of specimens in the collection and resulted in an updated taxonomic identification of the Calligrapha collection at the Royal Belgian Institute of Natural Sciences. The pictures of the specimens and their original labels, as well as the new information from this endeavor were placed in an online public catalogue. This study demonstrates a worked example of how digitization has led to a practical, useful outcome through cooperation with an end user and highlights the value of museum collection digitization projects.